The Chubut Group (Cretaceous, Golfo San Jorge Basin): A synthesis of its sedimentary petrography (Latin American Journal of Sedimentology and Basin Analysis, 2025)
This study presents a synthesis of petrographic analyses of the cretaceous Pozo D-129, Matasiete, Castillo, and Bajo Barreal formations in the Golfo San Jorge Basin, highlighting the influence of volcanic activity and sediment supply on the evolution of the Chubut Group. Data from outcrops in the San Bernardo Fold Belt and from the subsurface indicate that sandstone compositional variability was controlled by shifts in sediment source areas, linked to regional tectonic processes and active volcanism. Sandstones exhibit feldspatho-lithic and litho-feldspathic qFL, fQL, IQF to qLF composition detrital modes, with spatial and temporal variations in volcanic, pyroclastic lithic, feldspar and quartz components. The sediment sources for the outcrops in the San Bernardo Fold Belt include the Paleozoic igneous-metamorphic basement, Middle-Upper Jurassic volcanic and volcaniclastic rocks (Lonco Trapial Group), and acidic and pyroclastic sequences assigned to the Marifil Group. In contrast, the South Flank records a broader range of petrofacies, reflecting a combination of distal and local sources. In addition to the provenance of the Andes Cordillera, this sector received sediment contributions from Jurassic rocks exposed in the Deseado Region and older crystalline basement units. Andean volcanism dominates across all units, contributing direct volcanic ash fallout and reworked pyroclastic material.
Keywords: detrital modes; volcaniclastic input; sediment routing; provenance; multiple source areas